1974
DOI: 10.4039/ent106917-9
|View full text |Cite
|
Sign up to set email alerts
|

Control of Codling Moth Larvae in Harvested Apples by Methyl Bromide Fumigation and Cold Storage

Abstract: Can. Ent. 106: 913-916 (1974) Arthropod population densities were evaluated from nests of colonial ring-billed gulls (Larus delawarensis). Each nest was considered as being an island microhabitat in which a measurable population was concentrated. Despite significantly greater numbers of arthropods in larger than in smaller gull nests, population densities per nest dry weight were similar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…An earlier era of single tactic control of codling moth by organochlorine insecticides in the 1950s and later organophosphate insecticides required to achieve phytosanitary standards for export led to problems with insecticide resistance [4,5], reduced biodiversity [6], and unwanted residues on fruit [7]. Fumigation of fruit with methyl bromide was also developed as a phytosanitary treatment for certain markets [8]. Concern over the lack of sustainability of these technologies led to research and development of alternatives such as sex pheromones for apple pests [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…An earlier era of single tactic control of codling moth by organochlorine insecticides in the 1950s and later organophosphate insecticides required to achieve phytosanitary standards for export led to problems with insecticide resistance [4,5], reduced biodiversity [6], and unwanted residues on fruit [7]. Fumigation of fruit with methyl bromide was also developed as a phytosanitary treatment for certain markets [8]. Concern over the lack of sustainability of these technologies led to research and development of alternatives such as sex pheromones for apple pests [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies indicate that cold temperatures can be efficacious against codling moth larvae. Morgan et al (1974) reported greater than 67.5% mortality in codling moth larvae infesting 'Delicious' apples when held 5 weeks at 0.5°C RA. Moffitt and Burditt (1989) killed greater than 35,000 codling moth eggs at red-ring stage after 55 d at 2.2°C or less in RA.…”
Section: Discussionmentioning
confidence: 93%
“…Fumigation with methyl bromide at 32 g/m3 for 2 h kills all codling moth larvae in apples (Morgan et al 1974) and cherries (Anthon et al 1975). Lower dosages did not kill all larvae (instars 1-3) in cherries (Anthon et al 1977).…”
Section: Introductionmentioning
confidence: 92%